CORN PRODUCTION AT DIFFERENT PLANTING DEPTHS - Silva, A. P. F.; da Costa, D. J.; Vicente, D. L. C.; da Silva, A. A.; Pereira, C. S. (Revista Brasileira de Engenharia de Biossistemas, 2019)
Corn (Zea mays L.) is one of the most used and relevant cereals due to its nutritional properties, chemical composition and diversity of use, both in human and animal food. With the constant innovations in the agricultural sector, seeking better production and cost reduction, a growing interest arises in providing alternatives that maximize the productive results of the sector. In this context, the objective of this experiment was to analyze the results and variations of corn crop, in relation to its development and productivity, obtained at different planting depths. The experiment was implanted under field conditions, using the design in randomized blocks, consisting of 4 treatments and 4 replications, in 4 lines, spaced at 0.55 meters between lines and 16 meters in length, totaling 35.2m² per plot. Four treatments were used: 1, 2, 3 and 4, defined at 1 cm, 3 cm, 5 cm and 7 cm respectively. The following parameters were evaluated: emergence speed index, stem diameter, plant height and productivity. With this study, it was observed that the emergence velocity index is influenced by sowing depth, the lower the plant emerges. Regarding productivity, the result was inverse to the IVE, that is, the higher the depth, the better the productive index of the analyzed crop, ratified by the best rate of stem diameter, height and production.